Long-term effects of good handling practices during the pre-weaning period of crossbred dairy heifer calves - Silva, Luciana Pontes [UNESP]; Sant’Anna, Aline Cristina [UNESP]; Silva, Lívia Carolina Magalhães [UNESP]; Paranhos da Costa, Mateus José Rodrigues [UNESP] (Springer Nature, 2017)
The aim of this study was to determine whether applying good practices of handling during the pre-weaning period have long-term effects on behavioral and physiological indicators, health status, and average daily gain (ADG) of crossbred Bos taurus × Bos indicus heifer calves. During the pre-weaning period, 98 crossbred of Holstein × Gir heifer calves were allotted into three treatments: (1) good practices of handling + brushing (GPB; n = 25), (2) good practices of handling (GP; n = 25), and (3) control (n = 48). Every 2 months, four evaluation periods (EV1 to EV4) were conducted to record data. Behavioral indicators comprised time to drive (TD), flight speed (FS), flight distance (FD), and composite reactivity score (CRS). Physiological indicators of acute stress during handling comprised respiratory and heart rates. Health status comprised data regarding occurrence of most common diseases (i.e., pneumonia and anaplasmosis). Collected data were analyzed by using a linear mixed model for repeated measures, Tukey’s test, and chi-squared procedures. Treatment influenced (P < 0.05) TD, FS, and FD but not CRS (P = 0.78). From EV1 to EV3, the control calves had the lowest TD. The GPB group had lower FS than the control but did not differ from GP. The GPB group had lower FD means than the other two groups in EV2, EV3, and EV4. No differences (P > 0.05) due to treatment were observed on heart and respiratory rates, ADG, or occurrence of pneumonia and anaplasmosis. It was concluded that adoption of good practices of handling during pre-weaning period may lead to long-term positive effects.
Keywords: Animal welfare; Calf handling; Calves; Temperament